A Systematic Review of Mechanisms of Change in Body-Oriented Yoga in Major Depressive Disorders - Meister, Klara; Juckel, Georg (Pharmacopsychiatry, 2018)
Introduction Despite empirical evidence for the efficacy of body-oriented yoga as add-on treatment for major depressive disorder (MDD), the specific mechanisms by which yoga leads to therapeutic changes remain unclear. By means of a systematic review, we evaluate how the field is progressing in its empirical investigation of mechanisms of change in yoga for MDD.Methods To identify relevant studies, a systematic search was conducted.Results The search produced 441 articles, of which 5 were included, that empirically examined 2 psychological mechanisms (mindfulness, rumination) and 3 biological mechanisms (vagal control, heart rate variability [HRV], brain-derived neurotrophic factor [BDNF], cortisol). 2 studies found that decreased rumination and 1 study that increased mindfulness was associated with the effect of yoga on treatment outcome. In addition, preliminary studies suggest that alterations in cortisol, BDNF, and HRV may play a role in how yoga exerts its clinical effect.Discussion The results suggest that body-oriented yoga could work through some of the theoretically predicted mechanisms. However, there is a need for more rigorous designs that can assess greater levels of causal specificity.
Keywords: yoga; depression; treatment mechanisms